An in-vitro study to compare the flexural strength, flexural modulus, and impact strength of heat-cure PMMA, heat-cure PMMA with reinforcement, polyamide, and polyamide with nano-additive - Sarangi, Debarchita; Das, Sitansu Sekhar; Mohapatra, Abhilash (Journal of Nepalese Prosthodontic Society, 2025)
Introduction: All denture base materials require sufficient flexural and impact strength to withstand functional and para-functional forces. Conventional PMMA offers high flexural strength but limited impact resistance, whereas polyamide provides flexibility and higher impact resistance but lower flexural strength. Reinforcement with aluminium oxide micro-particles and nanoparticles has been suggested to improve mechanical properties. This study aimed to evaluate the effect of aluminium oxide microparticles and nanoparticles on the flexural and impact strength of PMMA and polyamide denture base materials.Methods: Four groups of denture base materials were tested: heat-cure PMMA (1A–1B), PMMA reinforced with 2.5% aluminium oxide microparticles (2A–2B), polyamide (3A–3B), and polyamide with 0.5% aluminium oxide nanoparticles (4A–4B). Ten specimens per group were fabricated for flexural and impact strength testing according to ADA No. 12 and ASTM D-256 specifications, respectively. Flexural testing was performed using an Instron Universal Testing Machine, and impact strength was measured with a CEAST Izod impact tester. Data were analyzed using one-way ANOVA with post hoc multiple comparisons; p < 0.05 was considered statistically significant.Results: Heat-cure PMMA (1A) exhibited the highest flexural strength (91.69 ± 13.66 MPa), which was significantly greater than that of reinforced PMMA and polyamide groups (p < 0.001). PMMA reinforced with aluminium oxide microparticles (2A) showed improved flexural strength compared to unmodified PMMA. Polyamide groups (3A, 4A) exhibited higher impact strength than PMMA groups, with no significant difference between polyamide with and without nano-additives.Conclusion: Aluminium oxide microparticle reinforcement improved the flexural strength of PMMA, whereas aluminium oxide nanoparticles in polyamide did not significantly enhance flexural properties. PMMA is preferable when high flexural resistance is required, while polyamide offers superior impact resistance and flexibility. Clinicians should select denture base materials according to functional requirements and esthetic needs.